MEDICAL STUDENTS’ PERSPECTIVES ON E-LEARNING DURING THE COVID-19 PANDEMIC IN INDONESIA - Sulelino, Renny; Ban Bolly, Hendrikus Masang; Blesia, Jhon Urasti (Universitas Gadjah Mada, 2023)
Background: Online learning, as one e-learning form, enables interactive learning experiences for students. However, undergraduate students in the medical programme of Cenderawasih University in Papua have been facing various challenges in their engagement with online learning activities during the Covid-19 pandemic. This study examined the perspectives of medical students about their online learning experiences during the university closure due to policy regarding the pandemic situation.Methods: A total of 125 students participated in an online survey using Google Forms, and the data extracted were subject to descriptive analysisResults: The results showed that despite some positive feedback about the online learning management, learning delivery, and motivation received, the students shared their online learning challenges in their interactions with lecturers and peers, their inability to undertake independent self-study, as well as their challenges in group discussions and practicum classes. Other challenges students experienced were difficulties in purchasing internet data and their limited access to learning resources and learning spaces.Conclusion: Taking the socioeconomic and cultural status and contexts of Papua, the most eastern province of Indonesia, this study contributes to the literature on e-learning in medical education in such contexts. Medical faculties in similar settings can also benefit from this study.